RELEVANSI PENGGUNAAN RESTORATIVE JUSTICE DALAM TINDAK PIDANA DENGAN AKIBAT KEMATIAN - Oktobrian, Dwiki; Basworo , Handityo; Dwi Cahyani, Enny; Ramadhani, Setiawan; Ahmad Naufal, Zahid (Universitas Kristen Satya Wacana, 2024)
The repositioning of victims within a more just criminal justice system has been advanced through the implementation of restorative justice, provided that victims give their consent. This article explores the historical development of restorative justice in Indonesia and examines its relevance to criminal acts resulting in death. Using a statutory and conceptual approach, the study finds that restorative justice was first introduced in 2012 as a mechanism to protect children in conflict with the law. Over time, its scope has broadened, including limited application to fatal offenses—specifically negligent deprivation of liberty leading to death (Article 334 of the Indonesian Penal Code) and negligent acts causing death (Article 359). Historically, the adoption of restorative justice in Indonesia centered on the protection of offenders, particularly juveniles, rather than addressing the rights or recovery of victims. Its application in fatal cases raises a conceptual issue, as death represents an irreversible harm that contradicts the restorative aim of repairing the damage done. Therefore, this article suggests the need for a unified legal framework governing restorative justice in Indonesia, with its role in cases involving death limited solely to a basis for sentence mitigation, rather than complete restoration.